2019
DOI: 10.1111/apa.14750
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual skills and verbal abilities were better in children aged six to seven years who were from more highly educated families and attended sports clubs

Abstract: Aim We explored the cognitive abilities, health behaviour and cardiorespiratory fitness of preschool Estonian children aged 6–7 and any association with parental education, attending sports clubs and gender. Methods Data were obtained from 256 children recruited from 13 randomly chosen kindergartens in Tartu, Estonia. Cognitive abilities were assessed using the modified Boehm Test of Basic Concepts – Third Edition. Objective physical activity (PA) intensity and sedentary levels were measured over seven days by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…In recent study with 6-to 7-year-old preschool children, no associations were found between BMI and FM with MVPA and VPA. 11 Earlier Note: The unstandardized regression coefficients (b) with its 95% confidence interval (CI), standardized regression coefficient (β), and P value are given for each association. P < .05 was considered statistically significant, and was marked in bold.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent study with 6-to 7-year-old preschool children, no associations were found between BMI and FM with MVPA and VPA. 11 Earlier Note: The unstandardized regression coefficients (b) with its 95% confidence interval (CI), standardized regression coefficient (β), and P value are given for each association. P < .05 was considered statistically significant, and was marked in bold.…”
Section: Discussionmentioning
confidence: 99%
“…Counts of 100 to 1999, 2000 to 3999, ≥4000 per min distinguished light PA (LPA), MPA, and VPA, respectively. 11,14,16 Time spent in MVPA was calculated as the sum of MPA and VPA. 14 Total awake wear time (AWT) was calculated as the sum of SB, LPA, MPA, and VPA.…”
Section: Assessment Of Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Parents reported their educational attainment, and this measure was based on the highest level achieved by the mother or father and categorised as university level or less. The parents were also asked whether their child belonged to a SC [16]. Written informed consents were obtained from the parents of all participants.…”
Section: Methodsmentioning
confidence: 99%